Análisis de la sentencia No. 077-13-sep-cc. Caso No. 0080-10-ep. Sobre la inconstitucionalidad de la reducción del monto de la pensión jubilar patronal (Jurisprudencia) - Cevallos Zambrano, Jennifer Lissette (2015)
The Ecuadorian Social Security Institute issued several resolutions recognizing the right to retirement pension his former employer servants and workers through C.I. resolution No. 127 of 19 November 2001.Seven years later issued new resolution, which corresponds to D.C. 218 of September 19, 2008, through which it is changed and therefore the values are reduced to sense-previously recognized- by way of employer retirement. The former employees and workers of the Ecuadorian Institute of Social Security, initiate protective action in order to protect their right to receive the amount of money set first by the institute, it means, the pension employer retirement it was determined in the resolution CI No. 127 of 19 November 2001. The judge A quo and the Court Ad quem accept protective action, and consequently suspend the administrative act contained in Resolution No. D.C. 218 of 19 September 2008, and force the Ecuadorian Institute of Social Security, to meet the benefits that have been recognized through employer retirement agreements. The Constitutional Court comes to the knowledge of the cause, for the extraordinary action of protection that the Ecuadorian Social Security Institute proposes, at which emits the judgment under analysis in this case.